Cognitive Empathy and Longitudinal Changes in Temporo-Parietal Junction Thickness in Schizophrenia - Karpouzian-Rogers, Tatiana; Cobia, Derin; Petersen, Julie; Wang, Lei; Mittal, Vijay A.; Csernansky, John G.; Smith, Matthew J. (Frontiers in Psychiatry, 2021)
Objective: Deficits in cognitive empathy are well-documented in individuals with schizophrenia and are related to reduced community functioning. The temporoparietal junction (TPJ) is closely linked to cognitive empathy. We compared the relationship between baseline cognitive empathy and changes in TPJ thickness over twenty-four months between individuals with schizophrenia and healthy controls. Methods: Individuals with schizophrenia (n = 29) and healthy controls (n = 26) completed a cognitive empathy task and underwent structural neuroimaging at baseline and approximately twenty-four months later. Symmetrized percent change scores were calculated for right and left TPJ, as well as whole-brain volume, and compared between groups. Task accuracy was examined as a predictor of percent change in TPJ thickness and whole-brain volume in each group. Results: Individuals with schizophrenia demonstrated poorer accuracy on the cognitive empathy task (p < 0.001) and thinner TPJ cortex relative to controls at both time points (p = 0.01). In schizophrenia, greater task accuracy was uniquely related to less thinning of the TPJ over time (p = 0.02); task accuracy did not explain changes in left TPJ or whole-brain volume. Among controls, task accuracy did not explain changes in right or left TPJ, or whole-brain volume. Conclusions: Our findings suggest that greater cognitive empathy may explain sustained integrity of the right TPJ in individuals with schizophrenia, suggesting a contributory substrate for the long-term maintenance of this process in psychosis. Cognitive empathy was not related to changes in whole-brain volume, demonstrating the unique role of the TPJ in cognitive empathy.